When Indirect Decompression Fails: A Review of 220 Consecutive Direct Lateral Interbody Fusions and Unplanned Secondary Decompression. Issue 16 (15th August 2021) - Morgan, Clinton D.; Walker, Corey T.; Godzik, Jakub; Ohiorhenuan, Ifije E.; Catapano, Joshua S.; Hemphill, Courtney; Uribe, Juan S.
Abstract : Study Design: A consecutive series of patients who underwent minimally invasive spinal surgery by a single surgeon at a high-volume academic medical center were studied. Objective: The objective of this study was to identify the prevalence, radiographic features, and clinical characteristics of patients who require unplanned secondary decompressive laminectomy or foraminotomy after lateral lumbar interbody fusion (LLIF). Summary of Background Data: LLIF indirectly decompresses the spinal canal, lateral recess, and neural foramen when properly performed. However, indirect decompression relies on endplate integrity, reasonable bone quality, and sufficient contralateral release so that ligament distraction can occur. Some patients have insufficient decompression, resulting in persistent axial low back pain or radiculopathy. Methods: Patients undergoing LLIF for radiculopathy or refractory low back pain were enrolled in a prospective registry. Preoperative and postoperative imaging, clinical presentation, and operative reports were reviewed from this registry. Results: During registry collection, 122 patients were enrolled (220 lumbar levels treated), with nearly even representation between men (64/122, 52.5%) and women (58/122, 47.5%). Overall, right-sided lumbar spinal approaches (74/122, 60.7%) were more common. Ultimately, 4.1% (five of 122) of patients required unplanned direct decompressive laminectomy or foraminotomy because of refractory radiculopathy and persistent radiographic evidence of compression at the index LLIF level. All patients for whom indirect decompression failed were men who underwent stand-alone LLIF and had radiculopathy contralateral to the side of the LLIF approach. Most patients (59.8%, 73/122) had evidence of graft subsidence (grade 0 or 1) or osteoporosis. Conclusion: We report a 4.1% rate of return to the operating room for failed indirect decompression after LLIF for refractory radiculopathy. Graft subsidence and osteoporosis were common in these patients. All five patients who required secondary decompressive laminectomy or foraminotomy underwent stand-alone primary LLIF, and the persistent radiculopathy was consistently contralateral to the initial side of the LLIF approach. Level of Evidence: 4 Abstract : Lateral lumbar interbody fusion (LLIF) indirectly decompresses the spinal canal and neural foramen. However, in this prospective registry, five patients required secondary direct decompression at the index LLIF level. Most had evidence of osteoporosis and graft subsidence, and all of these patients reported persistent radiculopathy contralateral to the approach side.